2002
DOI: 10.1111/j.0014-3820.2002.tb01456.x
|View full text |Cite
|
Sign up to set email alerts
|

The Recruitment Sweepstakes Has Many Winners: Genetic Evidence From the Sea Urchin Strongylocentrotus Purpuratus

Abstract: As a consequence of free spawning in the unpredictable nearshore environment, marine species with large fecundities and high pre-reproductive mortality may be subject to extreme variance in reproductive success. If the unpredictability of the ocean results in only a small subset of the adult population contributing to each larval cohort, then reproduction may be viewed as a sweepstakes, with chance events determining which adults are successful each spawning season. Such a reproductive sweepstakes scenario may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 34 publications
7
101
1
Order By: Relevance
“…It has been hypothesized that life history traits of marine freespawning populations have partially evolved as a result of the unpredictability of spawning success (Flowers et al, 2002). In species with high pre-spawning mortalities, selection might favour allocation of more resources to growth/maintenance than reproduction, resulting in a longer life-span and a wider variance in maturity-at-age.…”
Section: A Bet-hedging Strategy To Guarantee Successful Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been hypothesized that life history traits of marine freespawning populations have partially evolved as a result of the unpredictability of spawning success (Flowers et al, 2002). In species with high pre-spawning mortalities, selection might favour allocation of more resources to growth/maintenance than reproduction, resulting in a longer life-span and a wider variance in maturity-at-age.…”
Section: A Bet-hedging Strategy To Guarantee Successful Reproductionmentioning
confidence: 99%
“…While the apparent absence of real barriers for fish/larvae displacement in marine environments could lead to a depression of the extent of genetic differentiation between subpopulations (Ward et al, 1994), several studies have detected significant heterogeneity among recruits on a small spatial scale in marine species dispersing via pelagic larvae, including gastropods (Johnson and Black, 1982), bivalves (Hedgecock, 1994;David et al, 1997;Li and Hedgecock, 1998), echinoderms (Edmands et al, 1996;Moberg and Burton, 2000;Flowers et al, 2002) and fish (Ruzzante et al, 1996;Planes and Lenfant, 2002;Pujolar et al, 2006Pujolar et al, , 2007. Hedgecock (1994) proposed that such genetic heterogeneity is likely to result from a large variance in reproductive success of parents.…”
Section: Introductionmentioning
confidence: 99%
“…The observed homogeneity among winter samples contrasted with a marked differentiation among summer samples from the same locations, which was explained in part from changes in larval-source populations caused by seasonal changes in oceanographic conditions. Flowers et al (2002) argued that distinguishing between genetic patchiness due to gene flow among populations, or genetic drift within populations, is often impossible because the 2 processes occur simultaneously in most marine species' planktonic larval dispersal. The gene flow hypothesis implies the existence of different source populations, which contradicts field observations of a single reproductive area for European eel (Tesch 2003).…”
Section: Alternative Hypothesismentioning
confidence: 99%
“…In other surveys (Ruzzante et al, 1996;Moberg and Burton, 2000;Pujolar et al, 2006;, sweepstakes recruitment (Hedgecock, 1994) best explains the differentiation among cohorts but additional factors (for example, selection, spatial genetic variation, changes in larval delivery) could not be excluded. In contrast, some studies have found no reduced genetic diversity in recruits relative to estimates of diversity from adults (Flowers et al, 2002;Gilbert-Horvath et al, 2006;Rose et al, 2006;Calderó n et al, 2009), no measurable genetic differentiation of recruits over time (Gilbert-Horvath et al, 2006;Calderó n et al, 2009), no evidence of family structure (Hernbinger et al, 1997) and no reduction in effective population size (Poulsen et al, 2006) indicating little variance in reproductive success. It is evident therefore, that despite the prominence of stochastic larval supply events in the life histories of many marine animals no general trends can be derived from empirical observations.…”
Section: Introductionmentioning
confidence: 95%